Thermoreversible Gel Lubricants through Universal Supramolecular Assembly of a Nonionic Surfactant in a Variety of Base Lubricating Liquids - Yu, Qiangliang; Fan, Mingjin; Li, Dongmei; Song, Zenghong; Cai, Meirong; Zhou, Feng; Liu, Weimin (ACS applied materials & interfaces, 2014)
The present paper investigates a new type of thermoreversible gel lubricant obtained by supramolecular assembly of low-molecular-weight organic gelator (LMWG) in different base oils. The LMWG is a nonionic surfactant with polar headgroup and hydrophobic tail that can self-assemble through collective noncovalent intermolecular interactions (H-bonding, hydrophobic interaction) to form fibrous structures and trap base oils (mineral oils, synthetic oils, and water) in the as-formed cavities. The gel lubricants are fully thermoreversible upon heating-up and cooling down and exhibit thixotropic characteristics. This makes them semisolid lubricants, but they behave like oils. The tribological test results disclosed that the LMWG could also effectively reduce friction and wear of sliding pairs compared with base oils without gelator. It is expected that when being used in oil-lubricated components, such as gear, rolling bearing, and so on, gel lubricant may effectively avoid base oil leak and evaporation loss and so is a benefit to operation and lubrication failure for a long time.